Clinical and pharmacological basis of the use of testosterone drugs for hormonal replacement therapy for hypogonadism in men - N. I. Volkova; A. V. Safronenko; E. V. Gantsgorn; Yu. S. Degtyareva (Ожирение и метаболизм, 2022)
Hypogonadism is a condition associated with a decrease in the functional activity of the testicles, accompanied by a decrease in the level of androgens and (or) a violation of the process of spermatogenesis. It is known that androgens and their main representative, testosterone, are of fundamental importance for the development and maintenance of the reproductive and sexual functions of the male reproductive system. At the same time, low testosterone levels are associated with both reproductive and metabolic disorders, including phosphorus-calcium, fat, carbohydrate, and protein metabolism. In addition, to date, data have been accumulated on the correlation of hypogonadism with cardiovascular diseases, which once again emphasizes the problem of testosterone deficiency, especially for patients of the middle and older age groups. However, carrying out testosterone replacement therapy always requires a strict and competent choice of a «target audience» among patients from a specialist. Today, on the pharmaceutical market, there is a wide arsenal of testosterone-containing drugs in various forms for use, which have an unequal «efficacy-safety» profile. In this review, we have analyzed modern approaches to the diagnosis and treatment of hypogonadism, the selection of a target group of patients to obtain the most effective and safe treatment outcome and described testosterone preparations and their dosage forms with potential advantages and disadvantages. Thus, the information presented in the article is aimed at optimizing the management of men with hypogonadism.